PENGARUH CITRA INSTITUSI, PENGALAMAN, DAN KEPERCAYAAN MAHASISWA TERHADAP PERILAKU WORD OF MOUTH (WOM) PADA SEBUAH PERGURUAN TINGGI SWASTA DI BANDUNG - Yanti Dameria; Jacinta Winarto (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2026)
This study aims to analyze the influence of institutional image, student experience, and trust on word of mouth behavior among students at a private university in Bandung. A quantitative explanatory survey approach was employed to obtain empirical insights into the relationships among these variables.The findings indicate that institutional image, student experience, and trust play significant roles in shaping students’ word of mouth behavior. Apositive institutional image emerges as the strongest driver encouraging students to share favorable recommendations, while student experience and trust contribute to strengthening their attachment and willingness to communicate positive impressions about the university. The three variables are also found to operate simultaneously in enhancingthe likelihood of word of mouth behavior.This study emphasizes that strengthening institutional image, managing holistic student experiences, and building sustainable trust are strategic priorities for higher education institutions inoptimizing students’ roles as organic communicators of the university.